Development of high frequency 14 nm CNTFET model - Farhana, Soheli; Alam, A.H.M Zahirul (Elsevier Ltd, 2016)
Carbon nanotube field-effect transistor (CNTFET) is a nano scale electronics device that has excellent electrical proper to perform fast operation. In this research, a 14 nm CNTFET model has been proposed to operate in high frequency performance. The CNTFET model is developed by quantum capacitance and electrostatic capacitance to enhance the mode of nanotube transistor. It can be used for design of nanotube transistor circuits as well as to study performance. A model of the Carbon nanotube transistor with the influence of quantum capacitance and ballistic transport on the high-frequency properties of nanotube transistors is also analyzed in this research.